Forms of Al in soil and soil solution in a long‐term fertilizer application experiment. (10th October 2014) - Rutkowska, B.; Szulc, W.; Hoch, M.; Spychaj‐Fabisiak, E.; Goss, Michael
Abstract Under the conditions of a long‐term fertilizer experiment, this study aimed to determine the contents of total and exchangeable aluminium in soil as well as the Al concentration in the soil solution. Additionally, Al speciation was evaluated with the use of the MINTEQA2 software. The results obtained indicated that under the conditions of long‐term application of different mineral fertilizers or farmyard manure, the soil reaction changed to a great extent (pH 3.58–6.78). At the same time, the content of total Al in soil fluctuated from 18.85 to 22.13 g/kg and that of exchangeable Al ranged from 1.42 to 102.66 mg/kg. The concentration of Al in the soil solution was highly differentiated (5.19–124.07 μmol/L) as well as that of free aluminium ions (Al3+) (0–16.9 μmol/L). In acidic soils, aluminium complexes with organic matter are the predominant forms of Al in the soil solution. In soils with neutral soil reaction, there were no free aluminium ions. Soil liming and addition of organic amendment were the treatments that restricted the presence of toxic aluminium forms in soil.